Pengaruh Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah (DPRD) Terhadap Penggunaan Anggaran Pendapatan Dan Belanja Daerah (APBD) Di Kabupaten Minahasa Selatan - Goni, Renaldy; Rorong, Arie; Tampi, Gustaf Budi (Sam Ratulangi University, 2015)
Abstract: In carrying out oversight functions, the Regional Representatives Council (DPRD) equippedwith special rights that can support the effectiveness of the work as one of the institutions of control in thearea. and most importantly that in determining whether or not accepted the draft budget proposed by theexecutive, the Regional Representatives Council (DPRD) had a very big right. Based on an evaluation ofthe State Audit Board (BPK) of the Republic of Indonesia through the representatives of North Sulawesi,assess the use of the Regional Budget (APBD) South Minahasa, from Fiscal Year 2009 to 2012 Budgetgets a